Analisis Kinerja Batik Solo Trans Menurut Wisatawan Lokal sebagai Pengguna Moda Di Kota Surakarta - Rizky Arif Nugroho; Eko Budi Santoso; Cahyono Susetyo (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2018)
The transportation sector allows users to visit certain areas, such as tourist attractions. This study aims to determine the performance of Batik Solo Trans as a supporter of the tourism sector in the city of Surakarta.The paradigm in this research is rationalistic. The method used in this research is quantitative method by using ServQual analysis. Based on the analysis results, it is known that there are several main priorities in improving the performance of Batik Solo Trans according to local tourists related to tangibles, responsiveness, assurance, and empathy.The results obtained are (1) in general the performance of Batik Solo Trans has reached the level of compliance between importance and performance more than 80%, (2) there are some variables that need to be improved such as the presence of signal alarm lights, the presence of security officers, the density of roads, low crash rates, and tarifs corresponding to the economic conditions of the community.